KEANEKARAGAMAN DAN POTENSI FLORA DI GUNUNG HALIMUN DAN SEKITARNYA DI TAMAN NASIONAL GUNUNG HALIMUN - Uji, Tahan (BERITA BIOLOGI, 2002)
Gunung Halimun National Park is one of the largest remnants of the tropical rain forest left in Java. The forest in this area is an interesting site to be studied due to the richness,diversity and potential of its flora. Through the intensive explorations in Mt. Halimun, Mt. Ci Timur and Mt.Panenjoan, 275 species of plant have been collected.Six species of them are determined as a rare and vulnerable plants, namely Alyxia rcinwardlii, Elaeocarpus grandiflorus, Symplocos odoratissima, Calamus adspersus, C. ciliaris and Korthalsia junghuhnii;and 10 species as "new record", namely Aidia corymbosa, Calophyllum saigonensc, Cryptocarya mentek, llemiscolopia trimera, Litsea elliptica, Sonchlu helerophyllu, Phoebe elliplica, Sarcandra glabru, Sehefflera longifolia and Tetrameri.sla glabra. Based on litterature studied. 151 species out of 275 are potentialplants and the largest group is medicinal plants (60 species).Other data can be gathered as follows 42 species of timber, 19 species of ornamental plants, 16 species of fruits, 10 species of vegetables, 6 species of rattans, 4 species of forages and 4 species of dye and tannin producing plants.